Energy input is primary controller of methane bubbling in subarctic lakes. Issue 2 (24th January 2014) - Wik, Martin; Thornton, Brett F.; Bastviken, David; MacIntyre, Sally; Varner, Ruth K.; Crill, Patrick M.
Abstract Emission of methane (CH4) from surface waters is often dominated by ebullition (bubbling), a transport mode with high‐spatiotemporal variability. Based on new and extensive CH4 ebullition data, we demonstrate striking correlations (r2 between 0.92 and 0.997) when comparing seasonal bubble CH4 flux from three shallow subarctic lakes to four readily measurable proxies of incoming energy flux and daily flux magnitudes to surface sediment temperature (r2 between 0.86 and 0.94). Our results after continuous multiyear sampling suggest that CH4 ebullition is a predictable process, and that heat flux into the lakes is the dominant driver of gas production and release. Future changes in the energy received by lakes and ponds due to shorter ice‐covered seasons will predictably alter the ebullitive CH4 flux from freshwater systems across northern landscapes. This finding is critical for our understanding of the dynamics of radiatively important trace gas sources and associated climate feedback.